(untitled) (Tokyo, Japan, 2003)
The present project covers the second phase of the JIRCAS initiative to develop sustainable farming systems in area. It emphasizes practical aspects such as on-farm trials of the technologies, economic evaluation of new technologies and so on.
Keywords: Cropping systems,Agriculture; Economic aspects